Diffusion-weighted magnetic resonance images and blood perfusion of hemiconvulsion-hemiplegia-epilepsy syndrome - Nojo, Takeshi; Takao, Hidemasa; Makita, Kohzou; Miyata, Rie; Kohyama, Jun (Journal of Pediatric Neurology, 2007)
Diffusion-weighted magnetic resonance images and brain blood perfusion scintigraphy are useful tools in identifying the cause of cerebral lesions. We report serial simultaneous diffusion-weighted magnetic resonance images and brain blood perfusion scintigraphy of hemiconvulsion-hemiplegia-epilepsy syndrome. In this case, the involved hemisphere revealed high intensity on diffusion-weighted images and slight hyperperfusion on brain blood perfusion scintigraphy 7 days after the seizure. Accordingly, neurotoxic, rather than ischemic, cellular edema might be the cause of hemiconvulsion-hemiplegia-epilepsy syndrome in the acute phase.
Keywords: Diffusion MRI; SPECT; hemiconvulsion-hemiplegia-epilepsy syndrome